Pengaruh Citra Merek Sibolang Durian terhadap Keputusan Pembelian - ARIEZA, APRILYA; BUDIASA, I WAYAN; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
The Influence of Brand Image on Durian Sibolang Purchasing Decisions Consumer purchasing decisions in buying Durian Sibolang products are influenced by three factors of brand image, namely company image, user image and product image. These factors influence each other in the purchasing decision process leading to purchase decisions.This study aims to determine the brand image of Durian Sibolang products, to analyze the characteristics of respondents on purchasing decisions and to analyze the effect of brand image on purchasing decisions. Respondents in this study were all Durian Sibolang consumers who had previously bought Durian Sibolang. This study uses accidental sampling method with a sample size of 50 respondents.The method used is descriptive analysis and SEM (Structural Equation Modeling) using Smart PLS software. The results show that consumers of Durian in Sibolang were dominated by women aged <25 years whose highest education level is high school (currently studying or working), and have an income of > 3,000,000. The results of this study also show the effect of brand image on consumer purchasing decisions. It can be concluded that company image does not have a significant effect on purchasing decisions, but two other brand image factors, namely user image and product image, have a significant effect on purchasing decisions.